A Time to Dance - Angelo, AH; Kerr, Jessica; Roylance, Bayley (Victoria University of Wellington Law Review, 2015)
There is, as is declared in Ecclesiastes, a time for everything and in particular "a time to dance", "a time to rejoice", and "a time where every person should eat and drink and enjoy the good of their labours". The three authors here join celebrating the service of their colleague, mentor and friend by tendering some comparative comments on the law of Seychelles.